The Influence of Islamic Business Ethics Implementation on Traditional Traders in Pamekasan, Madura - Akbar, Farid; Yenny Kornitasari (Islamic Economics and finance in Focus, 2025)
The market has a role as a place to mingle and carry out buying and selling transactions for various products for all levels of society. The increasingly rapid economy currently requires various parties to improve their performance and business in order to be able to compete with other parties, including business owners trading in traditional markets. The 17 August Market in Pamekasan Regency is one of the largest traditional markets in Pamekasan Regency, which is located in East Java Province with the highest level of market development in Indonesia. Increasing demands encourage traders to use transaction methods that are less in accordance with Islamic law. For example, neglecting prayers, committing fraud such as reducing scales, unclear expiration dates for goods sold, traders being unfriendly to buyers, and treating buyers differently. So in this research an analysis was carried out of the influence of the variables Tauhid (X1), Balance (X2), Balance (X3), Responsibility (X4), and Ihsan (X5) on Trader Behavior (Y). Based on the calculation of multiple linear regression analysis, the five variables play a significant role in the Trader Behavior variable, with the Tauhid variable (X1) having the most dominant influence.